2005
DOI: 10.1021/ja0520565
|View full text |Cite
|
Sign up to set email alerts
|

A General Acid−Base Mechanism for the Stabilization of a Tetrahedral Adduct in a Serine−Carboxyl Peptidase:  A Computational Study

Abstract: The QM/MM MD and free energy simulations show that serine-carboxyl peptidases (sedolisins) may stabilize the tetrahedral intermediates and tetrahedral adducts primarily through a general acid-base mechanism involving Asp (Asp164 for kumamolisin-As) rather than the oxyanion-hole interactions as in the cases of serine proteases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
50
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(61 citation statements)
references
References 26 publications
11
50
0
Order By: Relevance
“…The results support our earlier conclusion that the general acid mechanism involving Asp164 is crucial for the stabilization of the tetrahedral intermediate during the catalysis and that the electrostatic oxyanion hole interactions may not be sufficient to generate a stable TI along the reaction pathway (15)(16)(17). Moreover, Asp164 is found to act as a general base during the formation of the acyl-enzyme from the tetrahedral intermediate and therefore plays multiple roles in the catalysis.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…The results support our earlier conclusion that the general acid mechanism involving Asp164 is crucial for the stabilization of the tetrahedral intermediate during the catalysis and that the electrostatic oxyanion hole interactions may not be sufficient to generate a stable TI along the reaction pathway (15)(16)(17). Moreover, Asp164 is found to act as a general base during the formation of the acyl-enzyme from the tetrahedral intermediate and therefore plays multiple roles in the catalysis.…”
supporting
confidence: 88%
“…The average active site structure for the kumamolisin-Assubstrate (GPH*FF) complex obtained from the QM/MM MD simulations is given in Figure 1A. Ser278 is the nucleophile that attacks the carbonyl carbon atom (C) of the substrate, while Glu78 and Asp164 act as the general base and acid catalysts, respectively (4)(5)(6)(7)(8)(9)(10)(15)(16)(17). Two additional residues, Glu32 and Trp129, interact with Asp82 of the catalytic triad through hydrogen-bonding networks.…”
Section: Structural and Dynamic Properties Of The Substratementioning
confidence: 99%
See 1 more Smart Citation
“…As discussed in our earlier papers, the corresponding methylation reactions are expected to be more efficient, as a part of the TS stabilization would be already reflected in the reactant complexes. [16][17][18][19][20][21] In contrast, for the methylation reactions involving N 1 , the reactant complexes (Figs. 3A and 7A) are significantly distorted from the corresponding TS structures (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…The SCC-DFTB approach has been used previously on a number of systems by us, and the results seem to be reasonable. [16][17][18][19][20][21] We have compared the energetic results obtained from the SCC-DFTB and B3LYP/6-31G** calculations for the methyl transfer in a simple model system that resembles the methyl transfer in PRMTs (see Supplementary data). It was found that the potential energy function obtained from SCC-DFTB is quite similar to that obtained from the B3LYP/6-31G** calculations.…”
Section: Methodsmentioning
confidence: 99%